PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN PADI ADAN KRAYAN (Oryza sativa L.) - Harfresen Harfresen; Rustam Baraq Noor; Iin Arsensi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
The purpose of the research was to the effect of row spacing on the growth of upland rice (Oryza sativa L.) Adan Krayan; and to find row spacing for better growth of upland rice Adan Krayan.The research carried out from July to October 2020 in Liang Bua Village, Krayan Barat su-district, Nunukan Regency.The research used Completely Randomized Block Design (CRBD) with four treatment of row spacing and five replications namely: no uniform as control (p0), 30 cm x 30 cm (p1), 40 cm x 40 cm (p2), and 50 cm x 50 cm (p3). The result of the research revealed that : (1) row spacing treatment affected significantly to very significantly on the plant height, number of leaf and number of a tiller at 30, 60, and 90 days after planting, and (2) the best of the growth was produced in 40 cm x 40 cm.